The Role of Islamic Banking in the Implementation of Cash Waqf - Fauzi, Muhammad Resty; Prasetyo, Wicaksana Dwi; Lestari, Dini (IKAMAS: Manajemen Pendidikan Islam, 2023)
The purpose of this research is to find out how the implementation and use of waqf cash. The research method used is descriptive qualitative. The literature review is used to find reference sources and articles related to the Implementation and Management of waqf money related to the title of the study. Islamic financial institutions receiving Cash Waqf have an important role in optimizing cash waqf. Because this waqf of money cannot be handed over directly to the nazhir, but must go through the Islamic Financial Institution receiving the cash waqf, in its implementation, this Islamic financial institution must be professional in managing the collection, system mechanisms, and requires accountability and integrity in the waqf report.